What To Do With CO2? Storage Vs. EOR Vs. CO2 As A Chemical Feedstock - Arachchige, U.S. P. R.; Sakuna, S.P.W (International Journal of Advanced Research and Publications, 2019)
Atmospheric carbon dioxide concentration tremendously increased over the years due to fossil-fuel based power generation, industrialization, and deforestation. Therefore carbon dioxide capture technologies are essential to maintaining a better living environment. However, there should be a utilizing method with captured carbon dioxide. There are mainly three mechanisms involving captured carbon dioxide, Permanently storage, enhanced oil recovery, and carbon dioxide as a chemical feedstock. All of them have an advantage as well as disadvantages over the others
Keywords: Carbon Dioxide capture, Storage, Enhanced Oil recovery, Chemical feedstock